Curiosité et pouvoir : les collections de l’empereur moghol Jahāngīr (r. 1605-1627) - Corinne Lefèvre (Etudes Epistémè)
Like so many Muslim and Christian princes of the early modern period, Jahāngīr (r. 1605-1627) cultivated royal collecting to the highest degree, and stands first among the Mughals in this respect. His reign is in any case the most fully documented: apart from the surviving objects, the texts that he personally wrote (Jahāngīr Nāma) or those that he closely supervised (Majālis-i Jahāngīrī) – not to mention the countless paintings he commissioned – all bear the mark of his insatiable curiosity towards the imperial microcosm he had inherited from his father Akbar (r. 1556-1605), but also vis-à-vis the wider world, whose Eastern and Western representatives flocked to the Mughal court. Jahāngīrī collections are here examined under the combined rubrics of knowledge and power. After briefly presenting the ambitious epistemic project to which they belonged, this essay highlights the ideological motivations underlying their assemblage: as shown by the typology of their contents, the imperial collections were meant to gather at court the marvels of the Creation and to proclaim by the same token the universality of the monarch’s power. The conclusion will examine how the most “exotic” (especially Western) elements of these collections were skillfully manipulated by the painters of the Mughal studio in order to create a series of powerful visual representations of Jahāngīr’s macrocosmic domination.